Pengaruh Celebrity Endorser, Harga, Dan Kualitas Produk Terhadap Keputusan Pembelian Produk Smartphone Xiaomi Di Xiaomi Center Palembang (Jurnal Manajemen dan Investasi (MANIVESTASI), 2024)
ABSTRACT This study aims to test the hypothesis of the effect of celebrity endorser, price, and product quality on purchasing decisions for Xiaomi smartphone products at the Xiaomi Center Palembang. The population of this research is all customers who want to buy and who have bought a Xiaomi smartphone at the Xiaomi Center Palembang. The sampling technique is purposive sampling with the criteria of respondents being consumers who have Xiaomi smartphones, respondents have made purchases on Xiaomi smartphone products at least once, respondents have seen youtubers review Xiaomi smartphone products on Youtube. The number of samples as many as 83 respondents. The research data analysis technique used multiple linear regression, correlation coefficient, and coefficient of determination.Based on the results of the study, it can be explained that the results of the t-test analysis of the celebrity endorser variable obtained a significance value of 0.013